So i got 90 4/7 reduced in fractions
Answer:
Daughter age = 3 years
Step-by-step explanation:
Let x be the age of the women and y be the age of the daughter.
Given:
After five year the sum of the women and daughter age = 40
![(x+5)+(y+5)=40](https://tex.z-dn.net/?f=%28x%2B5%29%2B%28y%2B5%29%3D40)
At present the sum of the women and daughter age
![x+5+y+5=40](https://tex.z-dn.net/?f=x%2B5%2By%2B5%3D40)
![x+y+10=40](https://tex.z-dn.net/?f=x%2By%2B10%3D40)
![x+y=40-10](https://tex.z-dn.net/?f=x%2By%3D40-10)
--------------(1)
So the sum of the present age is ![x+y=30](https://tex.z-dn.net/?f=x%2By%3D30)
The difference in their present age is 24 years.
![x-y=24](https://tex.z-dn.net/?f=x-y%3D24)
![x=24+y](https://tex.z-dn.net/?f=x%3D24%2By)
Now we substitute x value in equation 1.
![(24+y)+y=30](https://tex.z-dn.net/?f=%2824%2By%29%2By%3D30)
![24+2y=30](https://tex.z-dn.net/?f=24%2B2y%3D30)
![2y=30-24](https://tex.z-dn.net/?f=2y%3D30-24)
![2y=6](https://tex.z-dn.net/?f=2y%3D6)
![y=\frac{6}{2}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B6%7D%7B2%7D)
![y=3\ years](https://tex.z-dn.net/?f=y%3D3%5C%20years)
Therefore, the daughter age is 3 years.
Answer:
$110.37
Step-by-step explanation:
Assuming the monthly payment is made at the beginning of the month, the formula for the monthly payment P that gives future value A will be ...
... A = P(1+r/12)((1+r/12)^(nt) -1)/(r/12) . . . . n=compoundings/year, t=years
... 14000 = P(1+.11/12)((1+.11/12)^(12·7) -1)/(.11/12)
... 14000 = P(12.11)((1+.11/12)^84 -1)/0.11 ≈ P·126.84714 . . . . fill in the given values
... P = 14000/126.84714 = 110.37 . . . . . divide by the coefficient of P
They should deposit $110.37 at the beginning of each month.
The simplified expression of
is ![x^2+xy+y^2](https://tex.z-dn.net/?f=x%5E2%2Bxy%2By%5E2)
<h3>Complete question</h3>
Simplify the expression: (x³ + (-y)³) / (x - y)
Do not include parentheses in your answer.
<h3>How to simplify the expression?</h3>
The expression is given as:
![\frac{x^3 + (-y)^3}{(x - y}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3%20%2B%20%28-y%29%5E3%7D%7B%28x%20-%20y%7D)
Open the inner bracket
![\frac{x^3 -y^3}{(x - y}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3%20-y%5E3%7D%7B%28x%20-%20y%7D)
Apply the difference of two cubes to the numerator
![\frac{(x-y)(x^2+xy+y^2)}{(x - y}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-y%29%28x%5E2%2Bxy%2By%5E2%29%7D%7B%28x%20-%20y%7D)
Cancel out the common factors
![x^2+xy+y^2](https://tex.z-dn.net/?f=x%5E2%2Bxy%2By%5E2)
Hence, the simplified expression of
is ![x^2+xy+y^2](https://tex.z-dn.net/?f=x%5E2%2Bxy%2By%5E2)
Read more about expressions at:
brainly.com/question/723406
#SPJ1
Answer:
x = 5
Step-by-step explanation:
a² + b² = c²
x² + 12² = 13²
x² + 144 = 169
x² = 169 - 144
x² = 25
![\sqrt{x^2} =\sqrt{25}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%5E2%7D%20%3D%5Csqrt%7B25%7D)
x = 5